The Effect of Communication on Employee Performance with Team Work As a Moderating Variable - Irwan; Badaruddin; Ramadhani Kirana Putra; Dikky Mooy; Mansyur (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Communication is the key to the success or failure of a target achieved and carried out by an employee. If employees are trapped in an atmosphere of confusion but have good communication, researchers believe employees can resolve it through good communication. Based on this, this research aims to analyze the influence of communication on employee performance. In contrast to a number of previous studies, this research adds the Work Team variable as a moderating variable which is believed to strengthen the influence of the Communication variable on Employee Performance. This research is quantitative research with an explanatory approach which uses a number of previous studies related to Organizational Communication, Employee Performance and Work Teams as a reflection and is combined into the latest research and at the same time has differences from previous studies. This research uses primary data that researchers obtained from Bank Bukopin which is spread throughout Indonesia. The data was distributed via an online questionnaire with statements 1-5 containing the sentences strongly agree, agree, normal/so-so, disagree and strongly disagree. These data were analyzed using the smart PLS 4.0 analysis tool The result in this article show that the Communication variable has a positive relationship and a significant influence on Employee Performance because the P-Values are positive and are below the 0.05 significance level, namely 0.021. Apart from that, researchers also believe that the Teamwork variable can moderate the influence of the Communication variable on the Employee Performance variable because with good teamwork chemistry will arise which forms good communication and ultimately improves the performance of each employee. In line with this, the results from the second row of the third table of the flow coefficient show that the Teamwork variable can moderate the influence of the Communication variable on Employee Performance because the P-Values value is positive and is below the 0.05 significance level, namely 0.000. Thus, the first and second hypotheses in this study can be accepted and validated.